1997
DOI: 10.1046/j.1365-2141.1997.d01-2072.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a novel bleeding disorder with isolated prolonged bleeding time and deficiency of platelet microvesicle generation

Abstract: Summary. Platelet prothrombinase activity and microvesicle (MV) generation were measured in four patients from three unrelated families with a life-long bleeding disorder associated with slightly prolonged bleeding time and isolated defective serum prothrombin consumption, without platelet function abnormality or von Willebrand factor defect. MV generation was reduced in all the patients either after thrombin plus collagen or A23187 calcium ionophore stimulation, whereas, at variance with Scott syndrome, proth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 18 publications
(35 reference statements)
2
56
0
Order By: Relevance
“…Conversely, patients with an inherited bleeding disorder, Scott syndrome, develop severe hemorrhagic manifestations due to a defect in scramblase activity, leading to the lack of surface exposure of PS (thus resulting in an inadequate ability to promote a procoagulable state) and to the inability of platelets and other blood cells to generate MPs (59). Another bleeding disorder that results in a decreased capacity of platelets to shed MPs has also been described (60). In the same line of thought, our results showed that the levels of CD41a…”
Section: Discussionsupporting
confidence: 86%
“…Conversely, patients with an inherited bleeding disorder, Scott syndrome, develop severe hemorrhagic manifestations due to a defect in scramblase activity, leading to the lack of surface exposure of PS (thus resulting in an inadequate ability to promote a procoagulable state) and to the inability of platelets and other blood cells to generate MPs (59). Another bleeding disorder that results in a decreased capacity of platelets to shed MPs has also been described (60). In the same line of thought, our results showed that the levels of CD41a…”
Section: Discussionsupporting
confidence: 86%
“…43,44 Pedigree studies have shown that this defect equally affects males and females, consistent with an autosomal recessive inheritance pattern of the disorder. 42 To date, only 3 documented human cases of Scott syndrome have been reported. 42 The paucity of human cases has hindered genetic analyses of the trait.…”
Section: Membrane Remodeling and Microparticle Formation: Insights Frmentioning
confidence: 99%
“…42 To date, only 3 documented human cases of Scott syndrome have been reported. 42 The paucity of human cases has hindered genetic analyses of the trait. As the underlying defect seems to be the deficiency of phospholipid floppase, the initial candidate gene for Scott syndrome was the canonical phospholipid scramblase (PLSCR1).…”
Section: Membrane Remodeling and Microparticle Formation: Insights Frmentioning
confidence: 99%
“…36 Serum aliquots were collected after 1, 2, and 7 hours of incubation (at 37°C) and immediately combined with 3.2% sodium citrate (1 vol citrate: 9 vol serum). For the PT assay, the citrate serum was added to a bovine fibrinogen solution (Sigma) containing a final concentration of fibrinogen of 1.5 mg/mL.…”
Section: Prothrombin Consumption Testmentioning
confidence: 99%